2021
DOI: 10.1177/03635465211013709
|View full text |Cite
|
Sign up to set email alerts
|

Beach Chair Versus Lateral Decubitus Position: Differences in Suture Anchor Position and Number During Arthroscopic Anterior Shoulder Stabilization

Abstract: Background: Arthroscopic shoulder capsulolabral repair using glenoid-based suture anchor fixation provides consistently favorable outcomes for patients with anterior glenohumeral instability. To optimize outcomes, inferior anchor position, especially at the 6-o’clock position, has been emphasized. Proponents of both the beach-chair (BC) and lateral decubitus (LD) positions advocate that this anchor location can be consistently achieved in both positions. Hypothesis: Patient positioning would be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, beach-chair positioning was associated with a greater number of anchors placed than lateral decubitus in this cohort. Although our data set on number of anchors used is much smaller than the data presented by Baron et al, 1 the drastic difference in results shows that there may be significant surgeon bias when evaluating perioperative factors such as number and location of anchors. A randomized study design would be optimal to clarify perioperative differences between beach-chair and lateral decubitus positioning; however, surgeon preferences and total surgical volume within each position significantly limit the feasibility and validity of such a clinical trial.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, beach-chair positioning was associated with a greater number of anchors placed than lateral decubitus in this cohort. Although our data set on number of anchors used is much smaller than the data presented by Baron et al, 1 the drastic difference in results shows that there may be significant surgeon bias when evaluating perioperative factors such as number and location of anchors. A randomized study design would be optimal to clarify perioperative differences between beach-chair and lateral decubitus positioning; however, surgeon preferences and total surgical volume within each position significantly limit the feasibility and validity of such a clinical trial.…”
Section: Discussionmentioning
confidence: 59%
“…3,6,10 This is supported by the findings of a recent cross-sectional study comparing the number and location of anchors used between beach-chair and lateral decubitus positions for arthroscopic anterior shoulder stabilization. 1 The authors found that anchors were placed in the 6-o’clock portion of the glenoid more than 2 times as frequently when patients were in the lateral decubitus position, and a larger number of anchors were placed with lateral decubitus positioning as well. 1 Despite the differences in anchor utilization, the current study found no differences in redislocation or subjective instability rates between beach-chair and lateral decubitus positions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We find that performing bony Bankart repair in an arthroscopic fashion permits anatomic positioning of the osseous fragment and accommodates additional intra-articular work, if needed, while avoiding the necessity of large incisions or split/takedown of the subscapularis. We prefer to perform all arthroscopic procedures for instability in the standard lateral decubitus position with a beanbag due to the relative ease of humeral distraction and placement of inferior anchors, 11 although this technique can be applied without any adjustments in the beach chair position. While positioned laterally prior to draping, an exam under anesthesia is performed.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Lateral patient positioning has been reported to be advantageous for the performance and results of BR in a recent systematic review ( 17 ). The MOON shoulder group reported that surgeons using the lateral position for BR more frequently placed anchors in the inferior glenoid and at the 6-o'clock position, which are recognized as important to achieve a satisfactory repair ( 18 ). The MOON shoulder group also reported in their prospective study for anterior shoulder instability that the majority of patients (75.5%, 426 of 564) underwent BR as their surgical treatment ( 19 ).…”
Section: Options For Surgical Treatmentmentioning
confidence: 99%